2022
DOI: 10.1371/journal.pone.0260687
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variables drive plant species composition and distribution in the moist temperate forests of Northwestern Himalaya, Pakistan

Abstract: By assessing plant species composition and distribution in biodiversity hotspots influenced by environmental gradients, we greatly advance our understanding of the local plant community and how environmental factors are affecting these communities. This is a proxy for determining how climate change influences plant communities in mountainous regions ("space-for-time" substitution). We evaluated plant species composition and distribution, and how and which environmental variables drive the plant communities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…variable similar to [79]. Our results support the argument that mountain tree communities are sensitive to climate and, thus, able to reveal its effects sooner than others [56]. Variation of species is also explained by interaction of factors, including: Climate, topography and soil (6.5%), as well as climate and topography (6.3%) (Fig 6).…”
Section: Plos Onesupporting
confidence: 86%
See 2 more Smart Citations
“…variable similar to [79]. Our results support the argument that mountain tree communities are sensitive to climate and, thus, able to reveal its effects sooner than others [56]. Variation of species is also explained by interaction of factors, including: Climate, topography and soil (6.5%), as well as climate and topography (6.3%) (Fig 6).…”
Section: Plos Onesupporting
confidence: 86%
“…Divergent distribution patterns of species and community composition of mountain ecosystems are influenced by dramatic changes in environmental conditions over short altitudinal distance [33,49,55,56]. Nevertheless, human exploitation may be imposing constraints that result in environmental modification [57] causing a shift in species range [58] and thus influencing species composition [59].…”
Section: Tree Species Community Structurementioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly found that invasive plant species can drive plant community composition subcategories such as plant species diversity and abundance [ 26 , 29 , 30 ]. Non-metric multi-dimensional scaling ordination results are often used to show patterns or relationships among plant communities but can be used to determine drivers of plant community composition [ 61 , 62 ]. Rahman et al [ 62 ] determined various environmental variables as composition drivers, while Kahmen et al [ 61 ] showed species with specific traits such high productivity, competitive ability, and nutrient use efficiency to be potentially significant drivers of community composition and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Plant species composition and distribution is influenced by the soil characteristics (Yang et al, 2018). Across different sites soil properties such as, Ph, OC, OM among others show significant differences, that eventually impact the plant species composition (Rahman et al, 2022). The community composition and species distribution pattern is also regulated by the soil organic matter.…”
Section: Discussionmentioning
confidence: 99%